Perancangan Desain Jaringan Menggunakan UISP Design Center bagi Tenaga Pendidik dan Kependidikan Bidang TIK Kabupaten Semarang - Jefri Alfa Razak; Veronica Lusiana; Sariyun Naja Anwar; Mohammad Riza Radyanto; Endang Lestariningsih (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This community service project was motivated by the limited technical competency among TIK (Information and Communication Technology) personnel in Semarang Regency schools in designing optimal computer network infrastructure. This situation resulted in slow, unstable, and poorly managed digital learning services within these schools. The main objective of this activity was to enhance the competency of 24 TIK personnel to enable them to design efficient, secure, and professional networks tailored to their schools' needs. The solution provided was hands-on training using the UISP Design Center, a web-based network design platform. The training was conducted face-to-face over two days and covered hierarchical topology, VLAN and QoS management, and practical design simulation. Measurement results demonstrated a significant increase in the participants' cognitive competency, evidenced by the average score rising from 45.2% on the pre-test to 82.5% on the post-test. Participants successfully applied these concepts to produce accurate designs for network topology, logical segmentation, and Bills of Materials (BOM). The high level of participant satisfaction confirms the effectiveness of this training in closing the skill gap. This activity successfully enhanced the network planning capability of the partner schools.